Isolasi Senyawa Metabolit Sekunder Utama Ekstrak Etanol Kulit Batang Tumbuhan Mangrove (Avicennia spp.) - . Darminto; Alimuddin Ali; Iwan Dini (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2012)
DOWNLOAD PDFIn vitro examine of fractionated ethanol extract of bark Mangrove (Avicennia spp). showed high antibaterial activity. Repression test of extract formula showed that fish has a higher viability. Recent study has conducted to find the main compound as candidate prior to standardized product of phytopharmaca for future commercial purposes. The chromatography methods was  applied and  identification of  major compounds by analysis based on chemical test as well as spectral data of spectroscopic measurements. Study showed that main secondary metabolites in the form of alkaloid class of polar compounds. The white crystalline powder form characteristics has a melting point 172oC with molecular weight 232, and molecular formula is C12H12N2O3.   Key words: Main secondary metabolites, mangrove, Avicennia spp.